The economic valuation of AnGR: Importance, application and practice - Drucker, Adam G. (Food and Agriculture Organization of the United Nations, 2001)
The importance of AnGR valuation and its policy applications: Economics is about choice and the efficient allocation of scarce resources that have alternative uses. Rationally speaking, choices should be made in such a way as to maximise the "utility" or "welfare" obtained. The large number of AnGR at risk, together with the limited financial resources available for conservation, mean that there is a need to decide which breeds should be conserved and how this should be done. Economic valuation can play an important role in ensuring an appropriate focus for conservation efforts. Specifically, establishing economic values for animal genetic resources can contribute to policy and management decisions because they can be used to: i) guide resource allocation between biodiversity conservation and other socially valuable endeavours, as well as between various types of genetic resource conservation, research and Development; and ii) assist in the design of economic incentives and institutional arrangements for farmers/genetic resource managers and breeders. Identifying the value of AnGR can thus be used to support, inter alia: i) resource conservationists and government planners who need to identify such values in order to justify budgets; ii) Farmer's Rights supporters who want measures of the value in order to calculate compensation to farmers in developing countries and iii) the Convention on Biodiversity's (CBD) call for "the fair and equitable distribution of the benefits arising out of the utilisation of genetic resources" (Article i).